2010
DOI: 10.1007/s00384-010-0957-y
|View full text |Cite
|
Sign up to set email alerts
|

Anal fistula plug is a valid alternative option for the treatment of complex anal fistula in the long term

Abstract: Fistula tract treatment with the anal fistula plug is a safe and viable surgical option that should be offered to complex fistula patients. The reasons and risk factors for recurrence remain to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
3

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
1
18
1
3
Order By: Relevance
“…25 The influence of loose draining setons on the results of anal fistula plug surgery has been evaluated in several studies. 7,10,12,25,26 El-Gazzaz et al 7 observed significantly higher rates of success in patients who had undergone seton drainage before plug insertion. In contrast, Zubaidi et al, 10 Lenisa et al, 12 and O'Connor et al, 26 found no influence of the presence of draining setons on closure of the fistula.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…25 The influence of loose draining setons on the results of anal fistula plug surgery has been evaluated in several studies. 7,10,12,25,26 El-Gazzaz et al 7 observed significantly higher rates of success in patients who had undergone seton drainage before plug insertion. In contrast, Zubaidi et al, 10 Lenisa et al, 12 and O'Connor et al, 26 found no influence of the presence of draining setons on closure of the fistula.…”
Section: Discussionmentioning
confidence: 97%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] Two randomized clinical trials compared an anal fistula plug with an advancement flap for the treatment of anal fistula. 15,16 van Koperen et al 15 found a recurrence rate of 71% in the anal fistula plug group, which was not significantly different from the 52% recurrence rate in the advancement flap group, and no significant differences were seen in functional outcome or quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grundlagen und Indikationen des Analfistelplugs wurden 2007 in einem Konsensuspapier publiziert [58]. Die veröffentli-chen Literaturergebnisse bilden überwie-gend Beobachtungsstudien ab ( [8,39,47,48,51,79,82,94,132,153,156,175,196,197,229,240,241,257,269,282,283,295,322]; . Tab.…”
Section: Analfistelplugunclassified
“…Ein Vorteil für den Erfolg einer plastischen Fistelrekonstruktion scheint sich hierdurch jedoch nicht zu ergeben[182]. Andererseits spielt die Fadendrainage jedoch für die Plug-Anwendung eine wichtige Rolle, da der Durchzug des Plugs erleichtert wird[156].Tab. 4 Ergebnisse der Fadenmethode (Faden als Drainage, "loose seton") Faden zur Anwendung.…”
unclassified